Memorial formativo: habilidades em desenvolvimento web utilizando conhecimentos de JavaScript aprendidos durante o curso de Sistemas de Informação - SANCHES, Josuel de Souza (2024)
The purpose of this document is to outline the academic journey of student Josuel de Souza Sanches as he pursues a degree in Information Systems at the esteemed Federal University of Pará (UFPA), Cametá campus. This memorial details the challenges encountered throughout the learning process, significant decisions that were essential for the progression of his studies. In addition, the motivation for his more specific focus in the area of system development. The document also describes the hands-on experiences gained in web development and the use of tools that enhanced his learning and programming proficiency.